Pengaruh Penggunaan Media E-Learning Terhadap Kedisiplinan Siswa dalam Mata Pelajaran PABP Kelas VII di SMP Negeri 1 Ciwidey - Yusniar Puji Astuti (Journal of Teacher Training and Educational Research, 2024)
The objectives of this study are 1) To determine the use of E-learning media in class VII in PABP (Religious Education and Character Education) subjects at SMPN 1 Ciwidey. 2) To determine the discipline of class VII students in PABP subjects at SMPN 1 Ciwidey. 3) To determine the effect of using E-learning media on the discipline of class VII students in PABP subjects at SMPN 1 Ciwidey. The approach used in this study uses a quantitative approach. The method used in this research is descriptive method. The results in this study are, 1) the results of descriptive statistical testing of E-learning media get an average result of 45.62% with the most answers being "S" (agree). 2) the results of the descriptive statistical test of students' discipline got an average result of 40.17% with the most answers being "S" (agree). 3) In the E-learning media, the value of t count = 4.050 > 1.997 = t table, and Sig. = 0.000 < 0.05 (5%), so Ho is rejected. This means that E-learning media has a significant effect on student discipline. . The regression equation that connects the variables X with Y is y = 0.523x + 16,292, which means that the E-learning media has a positive effect on student discipline. This can be seen from the coefficient X =0.235 which is positive. Based on the analysis conducted, the E-leaning media has a positive effect on student discipline. Then the effect of E-learning media on student discipline is 20.4% (not good).